(untitled) (REMUNOM, 2025)
Pertussis, also known as whooping cough, is a respiratory infection caused by the bacterium Bordetella pertussis. This disease is characterized by intense and paroxysmal coughing, accompanied by general malaise. It is a notifiable disease that primarily affects unvaccinated age groups, such as infants, in whom it presents greater severity. Vaccination, universally accessible, is combined in the DTP vaccine (diphtheria, tetanus, and pertussis), administered in three doses with two boosters, and is fundamental for reducing cases. Despite this, there has been a noted reemergence of the disease in the current context. Therefore, this research aims to outline the epidemiological profile of pertussis cases in the state of Paraná between 2020 and 2024, using data available on the platform of the Department of Informatics of the Unified Health System (DATASUS).